2020
DOI: 10.1186/s12931-020-01450-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of comorbidities and prognosis in patients with COPD diagnosed with the fixed ratio and the lower limit of normal: a systematic review and meta-analysis

Abstract: Background: Currently, the diagnosis of chronic obstructive pulmonary disease (COPD) is not uniform, COPD guidelines recommend fixed ratio (FR), whereas ATS and ERS define airflow obstruction based on lower limit of normal (LLN). We aim to determine if there is difference between the two diagnostic criteria for morbidity, mortality, exacerbation. Methods: Four databases and all relevant studies from the references were searched from inception to June 25, 2019, to find studies that described the rate of comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…(25) No entanto, nem todos os estudos detectaram essa diferença. (26) Não conseguimos analisar a segunda categoria discordante para obstrução (GOLD−/LIN+), pois nenhum dos indivíduos de nossa amostra se enquadrou nessa categoria. Isso provavelmente se deve ao fato de que incluímos apenas indivíduos ≥ 40 anos de idade, visto que já foi demonstrado que o critério GOLD subestima a obstrução das vias aéreas em indivíduos entre 20 e 44 anos de idade.…”
Section: Discussionunclassified
“…(25) No entanto, nem todos os estudos detectaram essa diferença. (26) Não conseguimos analisar a segunda categoria discordante para obstrução (GOLD−/LIN+), pois nenhum dos indivíduos de nossa amostra se enquadrou nessa categoria. Isso provavelmente se deve ao fato de que incluímos apenas indivíduos ≥ 40 anos de idade, visto que já foi demonstrado que o critério GOLD subestima a obstrução das vias aéreas em indivíduos entre 20 e 44 anos de idade.…”
Section: Discussionunclassified
“…Moreover, the main purpose of the present study was to detect airway obstruction using spirometry in a primary adult care setting. A recent meta-analysis showed that individuals with airflow limitations, when evaluated with LLN or FEV 1 /FVC < 0.70 fixed-ratio criteria, show no significant difference regarding the risk of developing comorbidities [ 50 ]. According to Celli, the use of the fixed threshold of FEV 1 /FVC < 0.70 can be considered a useful, simple tool that has prognostic and practical value, thus helping to remove barriers to widespread use of spirometry [ 46 , 51 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Author details 1 Independent Administrative Agency, National Hospital Organization, Fukuyama Medical Center, Fukuyama, Japan. 2 Department of Hematology, Oncology, Allergy and Respiratory Medicine, Okayama University Graduate School of Medicine, Dentistry, and Pharmaceutical Sciences, Okayama, Japan. 3 First Department of Internal Medicine, Shinshu University School of Medicine, Mastumoto, Japan.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is characterized by airflow obstruction that is not fully reversible, leading to respiratory insufficiency and functional disability [ 1 , 2 ]. Existing therapeutic options for COPD can reduce the severity of symptoms, and the frequency and severity of exacerbations.…”
Section: Introductionmentioning
confidence: 99%